Efecto del cierre de la economía por pandemia en la recaudación tributaria del departamento de Loreto periodo 2020 - Tuesta Guerra, Antonio (2022)
One of the measures adopted by the Government to combat the COVID-19 pandemic was the total closure of the economy, and its subsequent gradual reopening, affecting all sectors. The objective of this research is to determine the effect of the closure of the economy due to a pandemic on the tax collection of the department of Loreto in the period 2020. Taking this objective into account, the present study is carried out of a Quantitative type, Correlational level and non-experimental design. The research concludes that the closure of the economy due to a pandemic has a negative effect on tax collection in the department of Loreto in the 2020 period, validated by the Correlation Coefficient r = -0.779862623; which shows a very good inverse statistical association between the independent variable (closure of the economy) and the dependent variable (tax collection). Income Tax was the group of taxes that showed the greatest contraction in tax collection, falling by a monthly average of S/ -7,395.50 thousand (-38.62%). In the same sense, the Third Category Income Tax was the tax that reported the greatest negative impact on tax collection due to the effect of the COVID-19 pandemic, in the 2020 period. On the other hand, the analysis of customs taxes shows that tax collection had a variable behavior throughout the entire 2020 period.